Revitalisasi Pecinan di Siak Sri Indrapura Sri Indrapura Spasca Kebakaran (2018-2022) - Fauzana, Muhammad Ikhsan; Erniwati, Erniwati (Lembaga Yasin AlSys, 2023)
This research discusses efforts to revitalize Chinatown in Siak Sri Indrapura after the fire that occurred on February 17 2018 coincided with Chinese New Year celebrations. In this fire tragedy, 54 houses burned down with losses estimated at 15 billion. Until now, efforts to revitalize a number of burned buildings have not yet been implemented. Due to the slow pace of revitalization efforts, quite a few Chinese people affected by the fire chose to build new business premises and residences. This will of course have a big impact on the development of socio-economic life as well as an impact on the tourism sector which is being worked on by the Siak Sri Indrapura Regency government. The aim of this research is to answer questions related to the revitalization of Chinatown in Siak Sri Indrapura which has never been completed. In this case the author uses a historical research method which consists of four stages consisting of Heuristics, Interpretation, Source Criticism, Historiography. The results of this research show that the delay in Chinatown revitalization in Siak Sri Indrapura is caused by various interrelated factors, some of which are limited financial resources, stakeholder disagreements, severe building damage, permits and regulations, community involvement, changes in priorities, political uncertainty. and economics, planning and management deficiencies, and technical and architectural difficulties.